Mengenal Kenikmatan Surga Melalui Penerapan Layanan Informasi Berbasis Al-Qur’an Pada Mahasiswa Bimbingan Dan Penyuluhan Islam - Jannati, Zhila; Hamandia, Muhammad Randicha (Bulletin of Counseling and Psychotherapy, 2021)
Recognition of the best place of return, namely heaven, is very important for the individual. By knowing the pleasures of heaven, humans will always compete in goodness. Because, Allah has prepared a gift in the form of heaven for those who believe and fear Him. This study has a purpose, namely to be able to find out how to apply Al-qur'an-based information services to introduce the pleasures of heaven to students of the Islamic Guidance and Counseling Study Program, Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. This study used qualitative research methods. Data were collected through data collection techniques, namely interview and observation techniques. The subjects of this study were 28 students of the Islamic Guidance and Counseling Study Program, Faculty of Da'wah and Communication at UIN Raden Fatah Palembang. The data analysis technique in this study used descriptive qualitative data analysis. The results of this study are (1) Hadith-based information services to introduce students to heaven are carried out in several stages, namely: (a) planning stage, (b) organizing elements and service objectives, (c) implementation stage, (d) assessment, and (e) follow-up and report stages, and (2) Through hadith-based information services, students can get a good introduction and understanding of heaven as the best place to return, namely regarding (a) the nature of heaven, (b) the urgency of heaven as the best place for humans to return, (c) the pleasures in heaven, and (e) how to reach heaven. From the results of the research above, it can be concluded that hadith-based information can be an alternative in introducing students to heaven as the best place to return.